Chinese Economic Coercion Against Taiwan A Tricky Weapon to Use - Tanner, Murray Scot (RAND Corporation, 2007)
Since the early 1980s, the cross-strait relationship between Taiwan and mainland China has exploded, driven by economic and political reforms. As a result, each would suffer great economic pain and dislocation in the event of a major disruption in that rapidly growing economic relationship. This monograph analyzes the political impact of that relationship and evaluates the prospects for Beijing to exploit it by employing economic coercion against Taiwan.